Я щас решу и напишу. Подожди немного
Dc`/ Htibkf
Всё решила

Ответы и объяснения

Лучший Ответ!
2013-12-08T19:21:26+04:00
1)  (x-3)^{2} + (x+4)^{2} - (x-5)^{2} = 17x+24

 x^{2} -6x+9+ x^{2} +8x+16- x^{2} +10x-25-17x-24=0

 x^{2} - 5x -24=0

a=1; b=-5; c= -24

D= b^{2} - 4ac

D=25-4*1*(-24) = 25+96=121

 x_{1} =  \frac{5+11}{2} = 8

 x_{2} = \frac{5-11}{2} = -3

Номер2
 \frac{ x^{2} }{5} -  \frac{2x}{3} =  \frac{x-5}{6} / *30

6 x^{2} -20x=5x-25

6 x^{2} -20x-5x+25=0

6 x^{2} -25x+25=0

D=625-4*6*25=625-600=25

 x_{1} =  \frac{25+5}{12} = 2 \frac{1}{2}

 x_{2} = \frac{25-5}{12} = 1 \frac{3}{5}
Сейчас 2 номер решу и выложу тоже